First report on daily activity and feeding behavior of Javan hawk-eagle (Nisaetus bartelsi) in the protected forest of Kondang Merak Beach, Malang, Indonesia - ALIFANDI R. ILMI; MUHAMMAD LUTHFI; DEWI ELFIDASARI; Y.S. HIDAYAT; DEWI M. PRAWIRADILAGA (Society for Indonesian Biodiversity, 2023)
Abstract. Ilmi AR, Luthfi M, Elfidasari D, Hidayat YS, Prawiradilaga DM. 2023. First report on daily activity and feeding behavior of Javan hawk-eagle (Nisaetus bartelsi) in the protected forest of Kondang Merak Beach, Malang, Indonesia. Biodiversitas 24: 6770-6779. The Javan Hawk-Eagle (JHE) (Nisaetus bartelsi) is an endemic bird of prey (raptor) on Java Island that is increasingly threatened due to land conversion, habitat destruction, and illegal hunting. These factors have led to its classification as a critically endangered species. There is a need to monitor one of the natural conservation areas in the southern region of East Java, namely the protected forest of Kondang Merak Beach, which serves as a habitat for Javan hawk-eagle to preserve the existence of this species. Therefore, this research aimed to understand and identify the daily activity and feeding behavior of Javan hawk-eagle in the protected forest of Kondang Merak Beach, Malang, East Java. The implication of this research is to provide ecological data for further research and disseminate information to the community to support conservation efforts of Javan hawk-eagle species in the protected forest of Kondang Merak Beach area. The methods used included field surveys, observation of daily activity and feeding behavior, collection of daily temperature data, habitat assessment, disturbance assessment, and interviews. Based on the observation of daily activity, the percentage of perching behavior was 71%, while flying behavior was 29%. The peak flying activity occurred between 9:00 and 12:00. Environmental factors such as temperature, rainfall, and human activities influenced daily activity in the conversation area. The observation of feeding behavior showed that the highest frequency belonged to the category of 23 occurrences, where the peak occurred between 14:00 and 17:00. Furthermore, the activity was affected by nesting seasons and the presence of other raptor species besides Javan hawk-eagle.